Pengaruh Media Baliho terhadap Pengetahuan Sikap dan Kepercaaan pada Petani Tentang Bahaya Merokok di Dalam Rumah di Desa Wiwitan - Akhyar Rahmatul Rohim; Indra Amanah; Risma Yanti Yamin (Indonesian Journal of Science and Public Health, 2024)
A cigarette is a roll or roll of tobacco rolled/wrapped in paper, leaves, or corn husks, as big as a pinky with a length of 8-10 cm, usually smoked by someone after burning the tip. Smoking is a habit that farmers do, the habit reaches inside the house. This habit can be minimized by intervening in those who work as farmers, because this activity is often and always done to relieve fatigue after work and it is very dangerous for all family members who live together in the house. Based on the World Health Organization (WHO) report, the number of smokers aged 15 years and over in the world is 991 million people in 2020. Therefore, the existing group of farmers is over the age of 15 years so that smoking activities should not be accustomed to being done in the house because of the dangers that will be caused very much. So the billboard media is a reference used to educate and provide information on what will happen if the smoking activity is carried out in the house. Purpose: This study aims to determine the effect of media billboards on knowledge, attitudes and beliefs in farmers about the dangers of smoking in the house in wiwitan village, lamasi sub-district, luwu district in 2024. Methods: this research is a type of quantitative research with a Quasi-experimental design approach